Risk Factors for Multidrug-Resistant Bacterial Infections in Hospital-Acquired Pneumonia at Cipto Mangunkusumo Hospital - Murwaningrum, Artati; Kamelia, Telly; Chen, Khie; Loho, Tonny; Abdullah, Murdani (SAFE-Network, 2024)
Multidrug-resistant (MDR) hospital-acquired pneumonia (HAP) is linked to high mortality, extended hospital stays, and increased healthcare costs. Identifying risk factors for MDR HAP is essential to formulate effective management strategies. This study analyzed the proportion of risk factors associated with MDR bacterial infections in HAP patients treated at Cipto Mangunkusumo General Hospital. Using a retrospective cohort design, data were collected from medical records of HAP patients hospitalized between 2015 and 2016. A total of 68 patients met the inclusion criteria, while 10 were excluded due to fungal or non-pathogenic bacterial growth in sputum cultures. Patients were categorized as infected with MDR or non-MDR bacteria based on the resistance profile of their initial sputum cultures. Descriptive analysis was conducted using Microsoft Excel to calculate proportions of risk factors, without applying inferential statistical tests due to the limited sample size. The incidence of HAP was 6.12 per 1000 admissions in 2015 and 6.15 in 2016. MDR bacterial infections were observed in 95% of cases in 2015 and 82.1% in 2016. Key risk factors for MDR infections included prior antibiotic use within 90 days (100%), albumin levels <2.5 g/dL (100%), Charlson Comorbidity Index ≥3 (95.9%), age >60 years (95.2%), hospitalization >5 days (92.5%), nasogastric tube (NGT) insertion (92.1%), prior ICU/HCU admission within 90 days (81.8%), and steroid use >10 mg/day for >14 days (28.6%). These results emphasize that most HAP cases were caused by MDR bacteria, with prior antibiotic use and low albumin as predominant risk factors, necessitating targeted interventions for at-risk populations.